Relationships between postural balance, rifle stability and shooting accuracy among novice rifle shooters - Mononen, K.; Konttinen, N.; Viitasalo, J.; Era, P. (Scandinavian Journal of Medicine & Science in Sports, 2007)
The present study examined the relationships between shooting accuracy and shooters' behavioral performance, i.e., postural balance and gun barrel stability, among novice rifle shooters in intra- and inter-individual levels. Postural balance and rifle stability were assessed in terms of anteroposterior (VELAP) and mediolateral (VELML) sway velocity of the movement of center of pressure, and horizontal (DEVH) and vertical (DEVV) deviation of the aiming point. The participants (n=58) performed 30 shots in the standing position at a distance of 10 m from the target. The data showed that shooting accuracy was related to postural balance and rifle stability, but only at the inter-individual level. The correlation coefficients between shooting score and behavioral performance variables ranged from -0.29 to -0.45. The stepwise multiple regression analysis revealed that the VELML and the DEVH as independent variables accounted for 26% of the variance in the shooting score. The results also suggested that postural balance is related to the shooting accuracy both directly and indirectly through rifle stability. As the role of postural balance appeared to be important in shooting performance, the use of additional balance training programs to improve a shooter's postural skills should be encouraged.